Buku Ilustrasi Pengenalan Kuliner Tradisional Nasi Kapau - Yosi Fitrah; Ariusmedi Ariusmedi (Institut Nalanda, 2023)
The Illustration Book of Traditional Culinary Introduction to Nasi Kapau is a book designed to introduce one of Minangkabau culinary dish, Nasi Kapau. This book aims to provide information about Nasi Kapau including its regional origin, the characteristics of the seller, the way the side dishes are arranged, the various side dishes, the historical area where they first appeared, and the differences from Nasi Padang. Currently there are still many people who cannot identify Nasi Kapau even though they are spread across various provinces in Indonesia. With the design of this book, it is hoped that Nasi Kapau will become more well-known and there will be no misunderstandings. The illustration that will be used in this design uses a semi-realist illustration style and takes the original color of the original object. The design method used is the glass box method with data collection methods through observation, interviews, literature studies and documentation. The data was then analyzed using the 5W=1H method. The design of this Kapau Nasi Kapau Traditional Culinary Illustration Book Design will use the title